A new transcription factor ATG10S activates IFNL2 transcription by binding at an IRF1 site in HepG2 cells. Issue 12 (1st December 2020) - Zhang, Miao-Qing; Zhao, Qiong; Zhang, Jing-Pu
ABSTRACT: IFNL2 is a potent antiviral interferon, but the regulation of its gene expression is not fully clear. Here, we report the regulation of ATG10S for IFNL2 transcription. Through sequential deletion of the IFNL2 promoter sequence, we found LP1-1, a fragment of the promoter responding to ATG10S activity. Subcellular localization and DNA immunoprecipitation assays showed ATG10S translocating into the nucleus and binding to LP1-1 . Online prediction for transcription factor binding sites showed an IRF1 targeting locus in LP1-1 . Luciferase assays, RT-PCR, and western blot analysis revealed a core motif (CAAGAC) existing in LP1-1, which determined ATG10S and IRF1 activity; individual nucleotide substitution showed that the functional nucleotides of ATG10S targeting were C1, A3, and C6, and the ones associated with IRF1 were A3 and G4 within the core motif. Co-immunoprecipitation assays revealed ATG10S combination with KPNA1/importin α, KPNB1/importin β, and IRF1. The knockdown of endogenous IRF1 increased ATG10S activity on IFNL2 transcription. These results indicate that ATG10S as a transcription factor competes with IRF1 for the same binding site to promote IFNL2 gene transcription. Abbreviations: ATG10: autophagy related 10; ATG10S: the shorter isoform of autophagy related 10; BD: binding domain; CM: core motif; co-IP: co-immunoprecipitation; GFP: green fluorescent protein; HCV: hepatitis C virus; IF: immunofluorescence; IFN: interferon; IRF: interferon regulatory factor; LP: lambda promoter; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; RLU: relative light unit; SQSTM1: sequestosome 1.